Risk Factors for Ductal, Lobular, and Mixed Ductal-Lobular Breast Cancer in a Screening Population - Phipps, Amanda I. (2010)
BACKGROUND: Biological distinctions between histologic subtypes of breast cancer suggest etiologic differences, although few studies have been powered to examine such differences. We compared associations between several factors and risk of ductal, lobular, and mixed ductal-lobular breast cancers. METHODS: We used risk factor data from the Breast Cancer Surveillance Consortium for 3,331,744 mammograms on 1,211,238 women, including 19,119 women diagnosed with invasive breast cancer following mammography (N=14,818 ductal, 1,602 lobular, 1,601 mixed ductal-lobular). Histologic subtype-specific risk factor associations were evaluated using Cox regression. RESULTS: Significant positive associations with family history and breast density were similar across subtypes. Hormone therapy use was associated with increased risk of all subtypes, but was most strongly associated with lobular cancer [hazard ratio (HR) = 1.46, 95% confidence interval (CI): 1.25–1.70]. Relative to nulliparous women, parous women had lower risk of ductal and mixed but not lobular cancers (HR = 0.80, 95% CI: 0.76–0.84; HR = 0.79, 95% CI: 0.68–0.93; HR = 0.96, 95% CI: 0.81–1.15, respectively). Late age at first birth was associated with increased risk of all subtypes. CONCLUSIONS: Similarities in risk factor associations with ductal, lobular, and mixed breast cancer subtypes were more pronounced than differences. Distinctions between subtype-specific associations were limited to analyses of hormone therapy use and reproductive history. IMPACT: This study is the second-largest to date of breast cancer risk factors by histology, and the first to report on risk associations with breast density. Additional studies are needed to better characterize subtype-specific associations with genetic, hormonal, and non-hormonal factors.